New Off-Board Solution for Predicting Vehicles’ Intentions in the Highway On-Ramp Using Probabilistic Classifiers (Student Abstract) - Kherroubi, Zine El Abidine; Aknine, Samir; Bacha, Rebiha (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
This paper proposes a new approach for predicting drivers’ intentions in a Highway on-ramp merge situation using a central road side unit (RSU) with probabilistic classifiers.